Author's rights in the digital age: how Internet and peer-to-peer file sharing technology shape the perception of copyrights and copywrongs (Libellarium: journal for research in the field of information and related sciences, 2016)
Author's rights and copyright law have gone through quite a few changes in the 'post-print' culture of binary systems, digital formations and techno-practices. Technological development supports new concept of author's rights by promoting free internet and digital market, as well as new contemporary experience of culture that is being rooted in digital technology, mass communication and the world of multimedia and virtuality. Though computer and digital technology have served both authors and users in various ways, they have also served as a very fertile ground for sharing copyrighted content thus leading to numerous copyright infringements and conflicts with the copyright law. The aim of this paper is to identify and analyze the ways in which computer and digital technology have given rise to new trends in the production (e.g. remix culture) and consumption (e.g. peer-to-peer file sharing technology) of culture, but also to determine how new forms of distribution, use and sharing of digital content changed and shaped the perception of authorship in the 21st century. In order to analyze the dynamic, nature and structure by which new digital and networking technologies are affecting the concept of authorship and author's rights and to test the consistency of previously established hypotheses, we conducted a survey amongst general public. Altogether 535 questionnaires were completed. Data was analyzed using SPSS tool and quantitative method of analysis. In the analysis special attention was given to both, the concept of authorship in the digital environment and the concept of peer-to-peer file sharing technology as not so new, but still very popular networked architecture for distributing, using and sharing digital content.Results have shown that most of the respondents use peer-to-peer file sharing technology to access, consume and/or share different cultural content (e.g. movies, music, books, etc.) while violating the rights of copyright holders. That is one of the main reasons why copyright holders and creative industry constantly find new ways to fight peer-to-peer networking technology, especially commercial file sharing, thus sometimes restraining cultural production and even technological development. This leads to conclusion that this new dynamic, decentralized and distributed networked environment grounded in digital democracy and participating culture of prosumers asks for new legal initiatives and solutions. The research shows that the basic understanding of authorship and the right's of authors and other creative workers in the context of Internet culture and digital media hasn't changed a lot, but, by reason of new available digital means of production and tools of consumption, users attitudes, habits and practices towards them have. To resolve this conflict, law needs to find new mechanisms
Keywords: copyright law; author's rights; digital culture; peer-to-peer file sharing; networking technologies